2013
DOI: 10.1016/j.jare.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

An early prediction of the maximum amplitude of the solar cycle 25

Abstract: A solar activity precursor technique of spotless event has been currently used to predict the strengths and the times of rise of the 11-year coming cycles. This simple statistical method has been previously applied to predict the maximum amplitudes and the times of rises of cycles 22 and 23. The results obtained are successful for both cycles. A developed version of the suggested method was previously used to make an early forecast of the characteristic parameters of the cycle 24. In this work the preliminaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The values show that the predicted peak of SC 25 changes by about 11 sunspots for every 1‐nT change in the assumed precursor Ap index. Recently, Helal and Galal () forecasted the SC 25 using the precursor technique of spotless events and obtained maximum amplitude and time of rise to be 118.2 and 4.0 years, respectively. While their rise time is only about 9 months different from our value of4.75 years, simulations from our HR‐NN model indicate that the peak value of SSN will agree with their value of ~118 only if the precursor Ap index value gets as low as ~5.2 nT.…”
Section: Discussionmentioning
confidence: 99%
“…The values show that the predicted peak of SC 25 changes by about 11 sunspots for every 1‐nT change in the assumed precursor Ap index. Recently, Helal and Galal () forecasted the SC 25 using the precursor technique of spotless events and obtained maximum amplitude and time of rise to be 118.2 and 4.0 years, respectively. While their rise time is only about 9 months different from our value of4.75 years, simulations from our HR‐NN model indicate that the peak value of SSN will agree with their value of ~118 only if the precursor Ap index value gets as low as ~5.2 nT.…”
Section: Discussionmentioning
confidence: 99%
“…The Solar Cycle 25 prediction of Helal and Galal [] used the new calibration of R Z and found that the number of spotless days was a better predictor than with the old calibration [as discussed in Pesnell , ].…”
Section: Progress In Solar Cycle Data Setsmentioning
confidence: 99%
“…For example, DeJager and Duhau [] refined a previous geomagnetic precursor ( aa ) prediction for Solar Cycle 24 and laid the groundwork for Solar Cycle 25. Helal and Galal [] used a correlation between the number of spotless days and the upcoming solar maximum to update an earlier prediction to R 24 = 91.6 ± 11.3 in 2013.4 and estimated Solar Cycle 25 will have R 25 = 118.2, peaking 4.0 years after the upcoming solar minimum. Yoshida [] used correlations between R Z before minimum with the upcoming solar maximum, splitting the even/odd cycles to derive R 24 = 81.3 and R 25 = 115.4 ± 11.9.…”
Section: Anticipating the Next Solar Cyclementioning
confidence: 99%
“…At least 13 predictions of the amplitude of Solar Cycle 25 already exist. Some were from before 2016 and use R Z (Dumitrache, 2011;Helal & Galal, 2013;Javaraiah, 2015;Kakad, 2011;Lampropoulos et al, 2016;Li et al, 2015;Miao et al, 2015;Yoshida, 2014;Zachilas & Gkana, 2015). Others report their results with S N (Gkana & Zachilas, 2016;Pesnell & Schatten, 2018) or as fractions of previous activity (De Jager & Duhau, 2012;Shepherd et al, 2014).…”
Section: Introduction To Solar Cycle Predictionsmentioning
confidence: 99%
“…Others report their results with S N (Gkana & Zachilas, 2016;Pesnell & Schatten, 2018) or as fractions of previous activity (De Jager & Duhau, 2012;Shepherd et al, 2014). The Solar Cycle 25 prediction of Helal and Galal (2013) used R Z to derive a correlation between the number of spotless days and the rise time. But Pesnell (2012) showed that the number of spotless days in S N was a more accurate precursor.…”
Section: Introduction To Solar Cycle Predictionsmentioning
confidence: 99%